What happens to the function f(x)=(x−1)2+1 when it becomes f′(x)=(13x−1)2+1? It is compressed toward the y-axis. It is stretched

Question

What happens to the function f(x)=(x−1)2+1 when it becomes f′(x)=(13x−1)2+1?
It is compressed toward the y-axis.
It is stretched away from the x-axis.
It is compressed toward the x-axis.
It is stretched away from the y-axis.

in progress 0
Latifah 2 weeks 2021-07-22T20:18:54+00:00 1 Answers 4 views 0

Answers ( )

    0
    2021-07-22T20:20:47+00:00

    I think the answer is the last one

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )